Neutrophils in Bronchoalveolar Lavage Fluid Indicating the Severity and Relapse of Pulmonary Sarcoidosis - Feng, Haoshen; Yan, Lili; Zhao, Yabin; Li, Zhenhua; Kang, Jian (Frontiers in Medicine, 2022)
Abstract Background: Pulmonary sarcoidosis is a highly heterogeneous granulomatous disease without specific symptoms and manifestations. Neutrophils in bronchoalveolar lavage fluid (BALF) have been proposed to indicate the severity and prognosis of pulmonary sarcoidosis, but this needs confirmation in patients from different populations due to the heterogeneity of the disease. This study aimed to determine the characteristics of patients with pulmonary sarcoidosis in northeastern China, and to explore the relationship between neutrophils in BALF and the severity of pulmonary sarcoidosis. Methods: We enrolled 432 patients diagnosed with pulmonary sarcoidosis in this retrospective study. The symptoms, extrapulmonary involvement, FVC% pred (forced vital capacity percentage predicted) and DLco% pred (diffusing capacity of lung for carbon monoxide percentage predicted) were recorded. BAL was performed in 319 patients, and the results of cellular examination of BALF were collected. A total of 123 patients who received corticosteroid treatment were followed up for at least 12 months, and the outcomes were recorded. Results: Cough was the most common symptom and cutaneous involvement was the most common extrapulmonary manifestation in 304 (70.4%) and 82 (19.0%) patients, respectively. The percentages of patients with high neutrophil counts in BALF (>3%) were higher at Stages 2 and 3 compared with Stages 0 and 1 (33.2% vs. 19.4%, P=0.007), although the percentages of neutrophils in BALF showed no difference between patients at Stages 0, 1, 2, and 3. Patients with high neutrophil counts in BALF had lower FVC% pred compared with the other patients (79.5%±18.2% vs. 84.9%±14.5%, P=0.025), and were prone to relapse after corticosteroids were tapered. High neutrophil counts in BALF were independently associated with relapse after corticosteroids were tapered in a binary logistic regression analysis (P=0.027). Conclusions: Patients with pulmonary sarcoidosis lacked specific symptoms and manifestations. The neutrophil count in BALF could indicate the severity and outcomes of pulmonary sarcoidosis.